Notæ & animadversiones in Gerardi Joannis Vossi libros tres de historicis latinis - Sandius, Christophorus Christophorus 1644-1680; Vossius, Gerardus Joannes 1577-1649 (Amsterdam Janssonius, 1677)
Christopher Sandius Jr. (1644-1680) was an Arian writer and publisher of Socinian works without himself being a Socinian. Following research by Lech Szczucki, it appears that Sandius Jr. was well educated by his rigorous father, Christopher Sandius Sr., a government official in Königsberg, who himself was later removed from his office for anti-Trinitarian sympathies. Sandius Jr. moved to Amsterdam and earned his living as an editor, translator and publisher, he became well-recognized among European intellectuals. Sandius Jr. promoted the view that Arianism was the high point of the theology of the Early Church. He also enjoyed close relationship with Spinoza, especially at the end of his life, when he became known as one of philosopher's most faithful followers.
Commentary on Vossius' 'De Historicis Latinis Libri III' (1627)
Extra information on Provenance: used to be in the possession of Francesco Maria Berio, Marchese di Salza (1765-1820). In 1791, he inherited the title of marchese, along with the elegant residence in the via Roma at Naples and the famous library and art collection which his father (Domenico Berio) had collected. He added to both the library and art collection. His acquisitions were of great significance. In the early 1800s, his literary salons were celebrated, attracting many notable figures including Gabriele Rossetti and Gioacchino Rossino. Berio wrote libretti for several Rossini operas including Otello and Ricciardo and Zoraide. Upon his death the greater part of the library was sold to William Ward (1750-1823), 3rd Viscount Dudley. This book also contains Ward's bookplate to rear endpaper.
Contains index
Ex libris Francesco Berio 'Marchionis Salsae' (plate) & William Ward 'Comme je fus' (plate)
Keywords: 17th Century (1601-1700); History; Crescendo; Netherlands